Characterization of the crosslinking process of silicone pressure-sensitive adhesives - Czech, Z.; Gorący, K. (Polimery, 2022)
The process of thermal crosslinking of silicone pressure-sensitive adhesives, catalyzed with dichlorobenzoyl peroxide, was investigated using DSC method. Crosslinking temperature as well as energy evolved during crosslinking process were measured. Peel adhesion and shear strength of thermally crosslinked silicone pressure-sensitive adhesives dependently on crosslinking agent concentration were determined. IR investigations confirmed the course of crosslinking reaction via formation of chemical bonds between methyl groups of silicone pressure-sensitive adhesive.